PEMBERDAYAAN EKONOMI BERKELANJUTAN MELALUI OPTIMALISASI PROGRAM CSR PT PASANGKAYU PADA UMKM LOKAL DI KELURAHAN MARTAJAYA - Andri Alamsyah; I Wayan Indrawan; Raihan Fatahillah; Phiter Boni Parubak; Moh Nur Fahreza; Dyo Moh Sabda; Catur Bintang rachmansyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service activity aims to analyze and optimize the implementation of the Corporate Social Responsibility (CSR) program of PT Pasangkayu in supporting the economic empowerment of local Micro, Small, and Medium Enterprises (MSMEs) in Martajaya Village, Pasangkayu District, Pasangkayu Regency, West Sulawesi, Indonesia. As part of PT Astra Agro Lestari Tbk, PT Pasangkayu implements its CSR program through four main pillars: Astra Creative, Astra Healthy, Astra Smart, and Astra Green. This activity focuses on the Astra Creative pillar, which includes MSME development, community productive business enhancement, and marketing digitalization. The method employed was Participatory Action Research (PAR), involving observation, interviews, Focus Group Discussions (FGDs), and direct assistance to beneficiary communities. The results indicate that the CSR program has contributed to the development of 11 MSME groups operating across seven major business sectors, benefiting a total of 475 households. The program has not only enhanced the business capacity of local communities but also strengthened market access, encouraged local product innovation, and increased community participation in economic development. Nevertheless, several challenges remain, including limited human resource capacity, low digital literacy, and restricted access to broader markets. Therefore, optimization strategies are needed through capacity-building initiatives for MSME actors, the enhancement of digital marketing capabilities, the development of partnership networks, and the implementation of a sustainable monitoring and evaluation system. This activity demonstrates that a participatory CSR program can serve as an effective and sustainable instrument for community economic empowerment.Keywords: Corporate Social Responsibility, Economic Empowerment, Micro, Small, and Medium Enterprises (MSMEs), Astra Creative, Martajaya.